THE RUSSIAN’S DIGITAL SOVEREIGNTY AS A TECHNICAL BASIS OF INFORMATION SECURITY - V. V. Bukharin (Vestnik MGIMO-Universiteta)
The article deals with the problem of the emergence of concept of "information sovereignty" in Russia, the prospects for its practical and theoretical introduction to the scientific revolution. The problem of "information sovereignty" in the normative documents of Russia, China and other Countries is examined. The focus of the article, first time in the domestic and foreign historiography, the technical aspects of independence in the field of digital technologies is analyzed. In this connection, the most important components of digital sovereignty is analyzed, technically ensuring national security. The author concludes that the main feature of the Russian technical resources to ensure the sovereignty of the information is fragmentary and uneven in the development of its components. The greatest progress has been made in the development of components such as the Russian search engines, social networks, national segment of "Internet"and the navigation system. Russian software and hardware require to ensure the accelerated development of information sovereignty, Russia's national security. The greatest attention should be Russian payment system, because this issue is directly dependent on the direction of development of the national economy. The problem of information sovereignty is largely related to issues of public decision-making, in bringing regulatory and legislative framework in line with the national security concept of the country.